Adaba and the South Wind A Myth from El-Amarna. (14th century B.C.) - mohammad, jihan (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The myth tackles constitutes one of the distinguished examples of Mesopotamian literature, and it tackles the quest for immortality, but the general situation of the currently known text of the myth is not sufficient to know its full details. What can be deduced from it is that Adaba was a man of wisdom from the Sumerian city of Eridu (Abu Shahren, southwest of Nasiriyah in southern Iraq). He was serving Enki, the Sumerian god of wisdom, loved by the people, supervising the preparation of food and hospitality during the practice of religious rites, and fishing from the nearby sea. The god Enki endowed Adaba with great intelligence and wisdom, and provided him with instructions about the order of the universe. Adaba set out one day on his boat near his city of Eridu (the Arabian Gulf now) hoping for abundant fishing that be served on the tables of religious rites, but he was surprised that a wind coming from the south, seemed to him in the form of a bird, blew so violently that he was thrown into the sea. In his rage he broke the wings of the south wind, which then ceased to blow. As a result, the sky god Anu (Sumerian: An) revolts against him, threatens him with punishment for his sin, and summons Adaba to appear before him in heaven. ‌The god Ea (Sumerian:Enki) showes mercy and advises Adaba to abstain from all that is offered to him of food and drink, because it would cause his death. But Anu, the sky god, offers Adaba what guarantees him immortality. however, ignorant of the truth, Adaba abstains and misses the opportunity of being immortal. The Text was discovered at the Amarna site, near the city of Minya in southern Egypt, and dates back to the 14th century BC. It is evidence of the wide spread of Mesopotamian culture.